Lithium ion batteries in electric drive vehicles - Pesaran, Ahmad A. (Society of Automotive Engineers. Electronic publications, 2016)
This special SAE publication is focused on lithium ion technologies in electric drive vehicles (HEVs, PHEVs, EVs, EREVs, mild HEVs with 48 V. and even conventional vehicles with start/stop technology) Ten SAE technical papers are included in this publication, which examines several relevant issues for the implementation of lithium ion technology and reviews solutions offered in addressing those issues.